Strategi Pengembangan UMKM Berbasis Digital Pada Bee’s Store - Muhammad Hafizh Naulir Ridho; Maharani Ikaningtyas (Yayasan Daarul Huda Kruengmane, 2023)
Micro and small enterprises, or MSMEs, are small businesses. Individuals, families, and businesses can all participate. Based on the facts, from the characteristics to the understanding, we can find this micro business in Law no. 20 of 2008. In the midst of these developments, the government is starting to pay more attention to the problems it is facing. Students conducted surveys and interviews with RW XI officials in the Semolowaru sub-district, Sukolilo District, along with the implementers of MSME activities in RWXI, Semolowaru Village. The survey activity was carried out using a question and answer system model as well as interactive discussions about how the dynamics experienced by MSME actors in Semolowaru Village with the Thematic KKN Student team on entrepreneurship and creative economy schemes. By using this kind of research, students can collect various information about UMKM Bee's Store. The development of science and technology with the emergence of Instagram as a digital platform is expected to be able to increase the sales of MSMEs in Semolowaru Village and maintain their existence by improving the quality of photography and visual content, increasing copywriting and content writing skills, increasing branding capabilities, and increasing digital marketing capabilities.